Developing Folktale-Based Student Worksheets to Improve Junior High School Students’ Collaboration Skills - Nafi’ah, Zahrotun; Utomo, Yudhi; Fatmawati, Denny (Education and Development Research, 2026)
Collaboration skills are an important part of 21st century learning that needs to be developed in teaching and learning activities. However, the results of observations and interviews with teachers at one of junior high school student in Malang, Indonesia showed that science learning has not fully facilitated optimal student collaboration. One alternative solution that can be done is through the development of student worksheets based on local folklore that is contextual and encourages group cooperation. This study aims to develop student worksheets based on the folklore